Modern tools for optimizing fluid management in dialysis patients: a comprehensive review - Sharad Patel; Sandhya Ashokkumar; Adam Green (BMC Nephrology)
Abstract Maintaining optimal fluid balance is crucial for patients with end-stage renal disease on dialysis, as both fluid overload and excess removal can lead to poor outcomes. Traditional approaches such as physical exam and chest X-ray have limitations when assessing volume status. This review carefully examines the tools that provide more precise options, including lung ultrasound, echocardiography, Venous Excess Ultrasound (VEXUS), bioimpedance analysis (BIA), and passive leg raise (PLR). We discuss the principles, supporting evidence, and practical uses of these techniques differentiating between static and dynamic methods to evaluate ultrafiltration tolerance. By integrating these modern techniques with clinical judgment, nephrologists can optimize fluid management in dialysis patients. While these tools show promise, further research is needed to establish standardized protocols and evaluate their impact on patient-centered outcomes.